The National Emergency Laparotomy Audit: impact for general surgical training and service provision - Boyd-Carson, Hannah (2020)
Emergency Laparotomies (Em Lap) are one of the most commonly performed emergency general surgical procedures worldwide. They are invasive abdominal operations performed to treat conditions such as intestinal obstruction or perforation. Mortality rates are high compared to planned general surgical procedures and the post-operative sequelae may represent significant burdens to patients, families, and healthcare systems. Prior to 2012, repeated observations were made regarding the deficiencies and variability of care received by the patients who required an Em Lap. Following this The National Emergency Laparotomy Audit (NELA) began in 2013.This collects detailed data about patients who have Em Lap and the care they receive within England and Wales, and hopes to improve outcomes for these patients.